Molecular timetrees reveal a Cambrian colonization of land and a new scenario for ecdysozoan evolution. - Rota-Stabelli, O; Daley, A; Pisani, D (2013)
Ecdysozoans have been key components of ecosystems since the early Cambrian, when trilobites and soft-bodied Burgess Shale-type ecdysozoans dominated marine animal communities. Even today, the most abundant animals on Earth are either nematode worms or plankton-forming crustaceans, whereas the most diverse are the insects. Throughout geological time, several ecdysozoan lineages independently colonized land, shaping both marine and terrestrial ecosystems and providing an adequate environment for successive animal terrestrialization. The timing of these events is largely uncertain and has been investigated only partially using molecular data. Here we present a timescale of ecdysozoan evolution based on multiple molecular data sets, the most complete set of fossil calibrations to date, and a thorough series of validation analyses. Results converge on an Ediacaran origin of all major ecdysozoan lineages (∼587-543 million years ago [mya]), followed by a fast Cambrian radiation of the pancrustaceans (∼539-511 mya), a Cambro-Ordovician colonization of land of different arthropod lineages (∼510-471 mya), and a relatively recent radiation of extant nematodes, onychophorans, and tardigrades (∼442 mya). Arthropods colonized land nearly synchronously with land plants. Further diversification within flying insects, nematodes and onychophorans might be related to the evolution of vascular plants and forests.